Metodologia para processamento do phase shift digital aplicado à técnica de shearografia - Almeida, Thiago Paiva (2016)
The adoption of the digital speckle pattern shearing interferometry, or speckle shearography, is well known in many fields, when it is necessary to measure microshifts in or out of the plane in biological and non-biological objects; based on the interferometer of Michelson, with the use of a piezoelectric transductor (PZT), in order to provide the phase shift of the fringes and, subsequently, improve the quality of the final image. The creation of images using a PZT shift, despite its generalized use, presents few disadvantages or limitations, such as cost of the device, difficulties in the application of the same shift in the mirror, repeatedly, and, when measuring the phase shift cannot be done in the dynamic object. The objective of this work was to digitally create images of phase shift, avoiding the mechanical adjustments of the PZT, testing them with the digital shearography method. The methodology was tested using a known object, an ASTM A36 cantilever beam under deformation. The results document the capacity of creating the deformation and curve map with reliability and sensitivity, reducing cost and improving sturdiness and accessibility of the digital speckle pattern shearing interferometry.